Faktor-Faktor Penghambat Program Pengentasan Kemiskinan oleh Pemerintah Desa Dolong B Kecamatan Walea Kepulauan Kabupaten Tojo Una-Una - Sidiki, Sandrina; Gobel, Lisda Van; Nusu, Olgha (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
This study aims to examine the poverty situation in Dolong B Village and the factors that influence community welfare. The method used was descriptive qualitative, with interviews with village officials and the community. The results revealed that the village's remote location is a major obstacle to increasing residents' income. Limited access to markets outside the village prevents agricultural and fishery products from being marketed optimally, resulting in underutilization of the existing economic potential, resulting in low daily income. Furthermore, this study identified micro-business opportunities that could be developed, such as home-based culinary arts, handicrafts, and skilled services. This potential is considered realistic for increasing family income, especially for housewives and village youth